Hepatoprotective and Antioxidant Role of Flower Extract of Abutilon indicum - Kalyani, Biradar (International Journal of Pharmaceutical & Biological Archive, 2011)
The hepatoprotective activity of the 70% Ethanolic extract of Abutilon indicum flowers was assessed using CCl4 induced hepatotoxicity in albino rats. The degree of protection against liver toxicity was determined by measuring the biochemical markers such as SGPT, SGOT, ACP, ALP and Bilirubin (Direct and Total). In addition morphological changes of liver like wet liver volume and wet liver weight were recorded. Further, histopathological examination of the liver was also studied. Silymarin at the dose of 25 mg/kg, p.o. was used as reference standard drug and it exhibited significant protection. In addition to the screening of hepatoprotective activity, in vitro antioxidant activity was studied by reducing power activity, superoxide anion scavenging activity and hydroxyl radical scavenging activity methods. Sodium meta bisulphate was used as a reference standard drug.